Navigating Employee Burnout in the Banking Sector: The Interplay of Emotional Intelligence and Organizational Support at Bank Sulselbar Masamba Branch - Serli Yandiani; S. Saharuddin; I Ketut Patra (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of emotional intelligence and organizational support on employee burnout at Bank Sulselbar, Masamba Branch. Utilizing a quantitative approach with a causal associative design, data were collected through structured questionnaires distributed to a total population of 36 employees. Due to the limited population size, a saturated sampling (census) technique was applied. Data analysis was conducted using Multiple Linear Regression through SPSS software version 30. The partial statistical results indicate that both emotional intelligence (t = -1.827; sig. 0.077 > 0.05) and organizational support (t = -1.214; sig. 0.233 > 0.05) have a negative but non-significant influence on employee burnout. However, the simultaneous testing (F-test) reveals that both variables collectively exert a significant effect on mitigating burnout, with a significance value of 0.016 < 0.05. The R-Square value of 0.220 indicates that the independent variables contribute 22% to the variance in employee burnout, while the remaining 78% is explained by other factors outside this research model. This study concludes that while internal psychological traits and external managerial resources are insufficient to reduce burnout independently, their integration acts as a critical strategic buffer against work exhaustion in the banking sector. Implications: Bank management is highly recommended to synergize specialized emotional coping training with structural organizational support, such as adjusting work demands and introducing psychological assistance programs, to effectively lower burnout levels.